Critical Discourse Analysis Of The "Opinion" Rubric In The April 2024 Edition Of Tempo Weekly Magazine - Rusdi; Wardiah, Dessy; Ali, Muhammad (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to uncover the hidden meaning within the Opinion section of Tempo magazine's April 2024 edition. The research employs a quantitative descriptive method with critical discourse analysis based on Van Dijk's model, utilizing data collection techniques through reading and note-taking. In analyzing the data, the researcher applies strategies of identification, clarification, and interpretation. The findings indicate that this study examines the structure and characteristics of opinion discourse in Tempo magazine's April 2024 edition using Van Dijk's approach. The key findings of this research include: (1) Structural analysis of the opinion text reveals alignment with Van Dijk's three discourse structures—macrostructure, superstructure, and microstructure. (2) The analysis of discourse characteristics identifies several features based on Van Dijk's theory, including action, context, history, power, and ideology.